Dakwah About Bitcoin, Connecting with Gen Z and Millennials on Faith and Digital - Aji, Gagas Gayuh; Prawitasari, Dian (Dakwah, 2025)
The rapid adoption of cryptocurrency, particularly among Gen Z and millennials, has raised significant ethical, financial, and religious questions in Islamic contexts. This study explores the role of dakwah in addressing cryptocurrency, with a focus on guiding Muslim communities toward Shariah-compliant financial practices. By employing content analysis of prominent Islamic preachers, such as Zakir Naik, Adi Hidayat, and Assim Al Hakeem, the research identifies recurring themes, including speculative risks (gharar), gambling-like behavior (maysir), and the lack of regulation. It also examines the nuanced rulings that differentiate permissible uses, such as spot transactions, from impermissible speculative investments. The findings highlight the critical role of preachers in educating their communities, emphasizing financial literacy, Shariah compliance, and ethical innovation. The study concludes with recommendations for leveraging digital platforms, promoting Shariah-compliant cryptocurrencies, and addressing the psychological factors, such as FOMO, driving impulsive investments. This research provides actionable insights for preachers to engage effectively with younger Muslim audiences in navigating cryptocurrency responsibly.